A novel image compression technology based on vector quantisation and linear regression prediction. Issue 2 (3rd April 2021) - Xu, Shuying; Chang, Chin-Chen; Liu, Yanjun
Abstract : In the information age, a digital image is an important media for people's daily interactions. Looking to maintain the quality of the restored image, how to maximise the compression of images has become a challenging topic. Vector quantisation (VQ) compression is an easy-operating image compression method that can compress images to 1/16th of the original size. Based on VQ compresses, a novel image compression method is proposed in this paper. The proposed scheme compresses the image depending on the result of linear regression prediction which can significantly increase the compression ratio.